Efficacy of trebananib (AMG 386) in treating epithelial ovarian cancer. (12th April 2016) - Al Wadi, Khalid; Ghatage, Prafull
ABSTRACT: Introduction : Epithelial ovarian cancer (EOC) is the leading cause of death among gynecologic cancers. The majority of women are diagnosed with advanced stage disease. It is considered a chemosensitive cancer with a high initial response rate to first-line platinum and taxane-based chemotherapy. However, most patients with advanced EOC will relapse with subsequent resistance to conventional chemotherapy and ultimately succumb to their disease. Therefore, new therapeutic agents and strategies are desperately needed to improve the outcomes in patients with advanced EOC. Areas covered : This review focuses on the use of Trebananib (a non-VEGF-dependent angiogenesis pathway inhibitor) in EOC. Angiogenesis has been recognized as an important process promoting EOC growth and metastasis. Targeting angiogenesis in EOC have been developed and studied with demonstrated clinical efficacy. Bevacizumab, a humanized monoclonal antibody, that targets vascular endothelial growth factor A (VEGF-A), has been the most well evaluated molecular targeted therapy in the treatment of advanced and recurrent EOC with proven clinical efficacy. However, VEGF-dependent angiogenesis pathway inhibitors are often associated with serious toxicities and drug resistance ultimately develops. Hence, new therapeutic approach targeting the angiopoietin-Tie-2 complex pathway (a non-VEGF-dependent angiogenesis pathway) has gained interest over the past few years as an alternative strategy to overcome VEGF-dependent anti-angiogenesis-related toxicity and resistance. Expert opinion : Targeting angiopoietin-Tie-2 pathway represents a promising alternative approach to tumor anti-angiogenesis with a distinct toxicity profile from the VEGF-dependent pathway inhibitors. However, there are still many questions to be answered regarding the optimal treatment schedules, maintenance regimens, duration of maintenance therapy, and the best combination strategy. Currently there is no reliable surrogate molecular, cellular, or genetic marker that would definitively predict response to anti-angiogenic therapy. Identification of certain relevant and predictive biomarkers in the future may optimize treatment's efficacy by distinguishing the subset group of patients with EOC that would derive the most benefit from existing antiangiogenic treatment regimens.